Emergent Hybrid Treatment of a Ruptured Scalp Arteriovenous Fistula with Eyelid involvement: Technical Note - Abaunza-Camacho, Juan Felipe; Vergara-Garcia, David; Perez, Francisco; Benavides, Camilo; Caballero, Alberto; Torres, Jorge; Riveros, William Mauricio (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background Scalp arteriovenous fistulas (AVFs) are a rare vascular disease usually presenting as a progressively increasing pulsating mass in the scalp. These lesions can be associated with mild to severe complications, including congestive heart failure. If ruptures, this pathology constitutes a life-threatening medical emergency because of its potential to cause severe bleeding and acute anemia.Methods We describe the case of a young woman with a ruptured Yokouchi type C scalp AVF with eyelid involvement.Results The patient presented with hypovolemic shock and acute anemia due to severe bleeding from the lesion. Emergent treatment through a combined endovascular and open surgical approach was required to stop bleeding and stabilize the patient.Conclusions Emergent and effective treatment is required to stop bleeding when a scalp AVF ruptures. A combination of endovascular embolization and microsurgical excision of the shunt is a treatment option.
Keywords: arteriovenous fistula; cirsoid aneurysm; endovascular therapy; open vascular surgery; scalp